Non-traditional open market operations: lessons from FDR's silver purchase program - Richard C. K. Burdekin; Marc D. Weidenmier (Claremont McKenna College, Department of Economics, 2005)
When faced with a liquidity trap, a traditional open market purchase will generally be ineffective. Theoretical studies have suggested that intervention in other markets could offer a means of escaping from this trap. We provide some empirical evidence on the importance of non-traditional open market operations by examining the economic effects of FDR's Silver Purchase Program. We employ a structural VAR to assess silver's role in influencing overall money growth, inflation and output over the 1934-1938 period. The results suggest that the US silver purchase program was effective and highlight the potential importance of non-traditional methods for reflating modern economies in a liquidity trap.
Keywords: 330